Association of Erythropoietin, Adiponectin and Leptin levels with Anemia in uremic diabetic patients (Under hemodialysis): - Al-Rubaâe, Salim M.; Daoud, Munaf S.; Al-Kadium, Tahrir E. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: End stage renal disease in patients with diabetes mellitus has been called a medical catastrophe of worldwide dimensions .It was recognized that anemia is a complication of diabetes, particularly in patients with diabetic kidney diseases. The purpose of the present study is to determine whether erythropoietin, adiponectin, and leptin levels correlate with anemia in uremic diabetic patients (under hemodialysis). Patients and Methods: The studied groups were comprised of (30) diabetic patients(9 patients with type1 and 21 type2 diabetes) with renal failure (group2) who had been under hemodialysis compared with (30) healthy controls (group1). Blood film was obtained in addition to blood tests include fasting serum glucose (FSG), glycosylated hemoglobin (A1c), insulin, urea, creatinine, uric acid, estimated glomerular filtration rate (eGFR), serum erythropoietin (EPO), Adiponectin (ADPN),and leptin. Results: It was found that uremic diabetic patients in group2(G2) had higher FSG, A1c, insulin and higher levels of urea, creatinine, uric acid and lower levels of eGFR when compared to healthy controls (P <0.05). Anemia was confirmed in the diabetic patients by Hemoglobin (Hb) and hematocrit (Hct) that were lower than healthy control (group1) (G1) (P<0.05).EPO, ADPN levels were increased in uremic diabetic patients as compared to control subjects (P <0.05). While, leptin levels were higher in type2 diabetes when compared to type1 diabetes and control subjects (group1) (P <0.05). There were positive significant correlations between (FSG and A1c), (Hb and Hct), (EPO and leptin), (EPO and Hct), (ADPN and urea). In addition there were significant negative correlations between (FSG and EPO), (A1c and leptin), (ADPN and leptin).Creatinine was negatively associated with Hb and Hct. ADPN was negatively associated with Hb in uremic diabetics. Conclusions: Anemia is a common accompaniment to diabetes, particularly in those with renal failure or under hemodialysis .Adipocytokines like leptin and adiponectin may involved with anemia in these patients. Leptin in the present study was positively associated with EPO levels (the hormone that stimulates red blood cells production in the bone marrow). ADPN was negatively associated with Hb. These elevated levels of ADPN may antagonize EPO and leptin to increase the hemopoiesis rate and Hb levels in uremic diabetic patients in addition to other factors involved with diabetes.